RECONSTRUCTION OR DECLINE: THE POSTWAR STATE OF UKRAINIAN EDUCATION IN GALICIA AS COVERED IN THE NEWSPAPER “DILO” (1918 – 1923) - KURYLYSHYN, Kostiantyn; HALIV , Mykola (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to identify the peculiarities of the reception by the authors and editorial staff of the newspaper “Dilo” of the reconstruction and transformation issues in Galicia in the first years after the end of the Great War. The chronological framework of the study is determined by the end of World War I in November 1918 and the official recognition by the Council of Ambassadors of the Polish sovereignty over Eastern Galicia in March 2023. The research methodology is based on the principles of historicism, systematicity, objectivity, as well as methods of criticism of historical sources, content analysis of media materials. Scientific novelty. For the first time in historical science, the coverage of the problems of reconstruction and transformation of education in Galicia 1918 – 1923 in Ukrainian newspaper “Dilo” was analyzed. Conclusions. Thus, the Ukrainian daily newspaper “Dilo”, despite censorship and persecution by the Polish occupation authorities, was one of the most informative press sources about the daily life of Ukrainian society in Galicia. The issue of education of the Ukrainians was one of the key issues on the newspaper's pages: about 50 publications (articles and short reports) focused on the issues of primary, secondary, vocational and higher education. The leading refrain of publications in the newspaper “Dilo” regarding Ukrainian schooling was the topic of oppression by the Polish authorities, which manifested itself in the closure of the Ukrainian primary and secondary schools, the ban on the use of the Ukrainian language at schools as the language of instruction and administration, the conversion of the Ukrainian schools into the Polish ones, and opposition to the opening of new Ukrainian educational institutions. Reports about successful educational projects of the Ukrainians (for example, about the elementary school in Berezhany, the Commercial School in Lviv, the private Ukrainian gymnasium in Yavoriv) were episodic and gave way to negative descriptions of the oppression of the Ukrainian schooling by the Polish authorities. The newspaper's editorial staff consistently advocated for the national character of the Ukrainian schools and reconstruction of the Ukrainian educational system that existed in Galicia before World War I. At the same time, it noted the deterioration of educational achievements and prospects for the Ukrainians due to Poland's incorporation and assimilation policies. In the newspaper chief focus is on the issue of the Ukrainian University creation in Lviv, the activities of the Petro Mohyla Scientific Lecture Society. We consider the analysis of the articles published in the newspaper “Dilo” on the activities of the Ukrainian educational public organizations that resumed their activities after World War I to be a promising direction of research. Key words: Newspaper “Dilo”, Post-War Reconstruction, Ukrainian education, schooling, educational policy, Polish Republic, Western Ukrainian People's Republic.